2006
DOI: 10.1172/jci27607
|View full text |Cite
|
Sign up to set email alerts
|

Cystamine and cysteamine increase brain levels of BDNF in Huntington disease via HSJ1b and transglutaminase

Abstract: There is no treatment for the neurodegenerative disorder Huntington disease (HD). Cystamine is a candidate drug; however, the mechanisms by which it operates remain unclear. We show here that cystamine increases levels of the heat shock DnaJ-containing protein 1b (HSJ1b) that are low in HD patients. HSJ1b inhibits polyQ-huntingtin-induced death of striatal neurons and neuronal dysfunction in Caenorhabditis elegans. This neuroprotective effect involves stimulation of the secretory pathway through formation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
173
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(183 citation statements)
references
References 70 publications
(128 reference statements)
8
173
0
2
Order By: Relevance
“…On that basis, the restoration of BDNF levels was actively targeted as a potential treatment for HD. In fact, a number of drugs proposed for HD treatment stimulate BDNF expression (e.g., riluzole [126], cystamine [120], memantine [121], ampakine [122], and CEP-1347 [123,124]). …”
Section: Bdnf Induces a Neuronal Addition To The Adult Striatummentioning
confidence: 99%
“…On that basis, the restoration of BDNF levels was actively targeted as a potential treatment for HD. In fact, a number of drugs proposed for HD treatment stimulate BDNF expression (e.g., riluzole [126], cystamine [120], memantine [121], ampakine [122], and CEP-1347 [123,124]). …”
Section: Bdnf Induces a Neuronal Addition To The Adult Striatummentioning
confidence: 99%
“…One of them, LM22A-4, restored respiratory regularity in female Mecp2 heterozygous mice [88,89], increased dendritic spine density in CA1 pyramidal neurons in organotypic slice cultures of male Mecp2 knockout mice (Miller, Longo, and LP-M, in preparation), and restored long-term potentiation at CA3->CA1 excitatory synapses in hippocampal slices from symptomatic female Mecp2 heterozygous mice (Li, Longo, and LP-M, in preparation). Finally, cysteamine (and its FDA-approved dimer cystamine) were shown to increase BDNF release by increasing heat shock DnaJ-containing protein 1b levels and inhibiting transglutaminase [90], which supports the Phase II/III clinical trial of delayed-release cysteamine (RP103) for Huntington disease. None of these compounds has reached human clinical trials for RTT.…”
Section: Neurotrophins and Growth Factors: Brain-derived Neurotrophicmentioning
confidence: 70%
“…93 While the specificity of cystamine for TG2 has been questioned because of its ability to inhibit caspases, 24,94 numerous studies have shown that cystamine can influence activities via TG-specific actions. For example, cystamine can enhance message of a large number of transcripts, including DNAJb10, an HSP40 chaperone that is decreased in postmortem brain extracts from HD patients; 90,95 it can also posttranscriptionally activate Nrf2 in a 3-Nitropropionic Acid lesioning; and it can enhance trafficking of brain-derived neurotrophic factor. 95 Thus, while cystamine has many off target effects from TG2 inhibition, its established effects on TG2 inhibition likely contribute in important ways to its therapeutic effects on neurodegeneration.…”
Section: Therapies and State Of Art For Inhibitorsmentioning
confidence: 99%
“…For example, cystamine can enhance message of a large number of transcripts, including DNAJb10, an HSP40 chaperone that is decreased in postmortem brain extracts from HD patients; 90,95 it can also posttranscriptionally activate Nrf2 in a 3-Nitropropionic Acid lesioning; and it can enhance trafficking of brain-derived neurotrophic factor. 95 Thus, while cystamine has many off target effects from TG2 inhibition, its established effects on TG2 inhibition likely contribute in important ways to its therapeutic effects on neurodegeneration. Additionally, cystamine partially protects from ischemic damage in the CA1 hippocampal region in gerbils 96 and it attenuates intracerebral hemorrhage-induced brain swelling and intracerebral hemorrhage-induced functional deficits.…”
Section: Therapies and State Of Art For Inhibitorsmentioning
confidence: 99%